Effect of membrane filtration on the fate of polychlorinated biphenyls in wastewater treatment. (January 2022) - Rodenburg, Lisa A.; Hermanson, Michael R.; Sumner, Amy L.
Abstract: The Spokane River is impacted by levels of polychlorinated biphenyls (PCBs) that have triggered fish consumption advisories and exceed water quality standards. Select wastewater treatment plants (WWTPs) on the river have been upgraded from secondary (biological) treatment to tertiary treatment in the form of membrane filtration to address phosphorus contamination. Because membrane filtration is effective at removing particles, it is likely to reduce PCB concentrations in the effluent as well. In this work, PCBs measured in the influents and effluent of several WWTPs discharging to the river were examined. Implementation of membrane filtration reduced PCB concentrations in the effluent (and therefore PCB loads to the river) by 33% at a facility that produces recycled and virgin paper and by ∼55% at municipal WWTPs, compared to secondary (activated sludge) treatment. Largest reductions in concentrations in effluent and loads were achieved for higher molecular weight (MW) PCB congeners (i.e. those with six or more chlorines), homologs, and formulations. The more modest reductions in effluent concentrations achieved at the paper WWTP may be due to the mix of PCBs in the wastewater there: it contained primarily the low MW Aroclor 1242 (presumably from carbonless copy paper) and PCB 11 (3, 3′-dichlorobiphenyl) possibly from pigments. PCBs that appear to be associated with silicone products such as caulk, tubing, and o-rings are relatively more abundant in the effluent of some plants compared to the influent, suggesting that these congeners arise from contamination during sampling or from within the plant itself. At some WWTPs, this contamination accounts for nearly a third of PCBs measured in the effluent. Graphical abstract: Image 1 Highlights: Polychlorinated biphenyls were measured in wastewater influents and effluents. Municipal plants and a mill making paper with recycled content were sampled. Samples were collected from secondary treatment as well as membrane filtration. Membrane filtration reduced PCB loads to receiving water by ∼55% at municipal plants. Membrane filtration reductions were less for PCB 11 and Aroclor 1242 at a paper mill.